2020
DOI: 10.3390/ma13092128
|View full text |Cite
|
Sign up to set email alerts
|

Hot Corrosion and Mechanical Performance of Repaired Inconel 718 Components via Laser Additive Manufacturing

Abstract: Hot corrosion is one of the crucial failure modes of Ni-based superalloy components operating at high temperatures, which inevitably affects the subsequent mechanical properties of the alloys. In this research, damaged Inconel 718 alloy components with a pre-made trapezoid groove are repaired using laser additive manufacturing technique, and the change mechanisms of the microstructure and tensile properties of the repaired Inconel 718 alloy due to the hot corrosion in the salt mixture of 87.5 wt.% Na2SO4 + 5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Figure 16 c,d shows the cross sections of grooves filled by DMD without and with prior laser remelting. Similar to the findings of Zhang et al [ 25 ], there is a high bonding quality for both conditions, without bonding defects. The specimen with prior laser remelting shows a more regular bonding depth, especially in the inclined wall area.…”
Section: Resultssupporting
confidence: 90%
“…Figure 16 c,d shows the cross sections of grooves filled by DMD without and with prior laser remelting. Similar to the findings of Zhang et al [ 25 ], there is a high bonding quality for both conditions, without bonding defects. The specimen with prior laser remelting shows a more regular bonding depth, especially in the inclined wall area.…”
Section: Resultssupporting
confidence: 90%
“…It was found, that the LENS could be successfully applied for the repair process and prevent effectively the phase transformations on the border of the cladding and substrate material resulting from the extremely high temperature. Zhang et al [ 27 ] performed the repair of the Inconel 718 components by means of laser additive manufacturing. In this study, the Inconel 718 was deposited on the substrate of the same material with a trapezoid grove by a fiber-coupled diode laser system (Laserline LDF400–2000, Mülheim-Kärlich, Germany) which was characterized by the wavelength of 980 nm and maximum laser power of 2 kW.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the molybdenum addition transforms the Laves phase morphology and decreases the segregation zone around the Laves phase. Moreover, the research of Zhang et al [ 27 ] presents, that the laser repair technology applied for the Inconel 718 alloy components led to elemental precipitation and the occurrence of the Laves phase. It could be concluded, that the process parameters proposed by the authors in a recent study enable a slight reduction of a phase transformation that occurred due to the high temperature resulting from the relatively high laser power of 900 W.…”
Section: Resultsmentioning
confidence: 99%
“…As previously stated, this phase is detrimental to Inconel 718 mechanical properties as it reduces strengthening phases such as γ" from being formed (Witzel, Stannard, Gasser, & Kelbassa, 2011;Zhang Q. , Zhang, Zhuang, Lu, & Yao, 2020). As Laves formation is promoted by increased Nb and Mo segregation, this can be reduced by using a dwell time between depositing adjacent tracks and subsequent layers.…”
Section: Laves Phasementioning
confidence: 99%
“…To mitigate elemental segregation, and subsequent formation of Laves, it is suggested that process conditions such as heat input, cooling rate and thermal gradients should be controlled (Radhakrishna & Prasad Rao, 1997) The dominant microstructure obtained for DED-L Inconel 718 consists of columnar dendrites elongated in the direction towards the heat sourceessentially consisting of γ-dendrites and interdendritic Laves (Jelvani, Razavi, Barekat, Dehnavi, & Erfanmanesh, 2019;Smith, et al, 2016;Zhao, Chen, Lin, & Huang, 2008;Zhang Q. , Zhang, Zhuang, Lu, & Yao, 2020;Mantri, et al, 2021). Laves forms irregularly, with morphology differing between laser powers (Zhu, Xu, & Gu, 2018).…”
Section: Laves Phasementioning
confidence: 99%